Micropatterning control of tubular commitment in human adult renal stem cells. (July 2016) - Sciancalepore, Anna G.; Portone, Alberto; Moffa, Maria; Persano, Luana; De Luca, Maria; Paiano, Aurora; Sallustio, Fabio; Schena, Francesco P.; Bucci, Cecilia; Pisignano, Dario
Abstract: The treatment of renal injury by autologous, patient-specific adult stem cells is still an unmet need. Unsolved issues remain the spatial integration of stem cells into damaged areas of the organ, the commitment in the required cell type and the development of improved bioengineered devices. In this respect, biomaterials and architectures have to be specialized to control stem cell differentiation. Here, we perform an extensive study on micropatterned extracellular matrix proteins, which constitute a simple and non-invasive approach to drive the differentiation of adult renal progenitor/stem cells (ARPCs) from human donors. ARPCs are interfaced with fibronectin (FN) micropatterns, in the absence of exogenous chemicals or cellular reprogramming. We obtain the differentiation towards tubular cells of ARPCs cultured in basal medium conditions, the tubular commitment thus being specifically induced by micropatterned substrates. We characterize the stability of the tubular differentiation as well as the induction of a polarized phenotype in micropatterned ARPCs. Thus, the developed cues, driving the functional commitment of ARPCs, offer a route to recreate the microenvironment of the stem cell niche in vitro, that may serve, in perspective, for the development of ARPC-based bioengineered devices.